2022
DOI: 10.1002/lim2.64
|View full text |Cite
|
Sign up to set email alerts
|

Insights into optimising education for patients living with diabetes mellitus: A model for the post‐pandemic era, informed by survey data

Abstract: Background Patient education represents the key element in the management of diabetes mellitus (DM) and has changed dramatically during the last 3 years. Uptake of structured education is poor, and patient perception of received education varies greatly. The purpose of this study was to assess patients’ perception of adequacy of delivered education, barriers to attending structured courses and preferences for ongoing DM‐related education. Methods Patients living with Type 2 DM attending diabetes clinics were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Finally, Hanson et al (2022) identified patient preferences in delivery methods for diabetes education session. They found that preferences for diabetes education were almost equally divided between those preferring in-person education and those preferring virtual education opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Hanson et al (2022) identified patient preferences in delivery methods for diabetes education session. They found that preferences for diabetes education were almost equally divided between those preferring in-person education and those preferring virtual education opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Goff [17] found that care providers in London caring for African-Caribbean patients felt additional training in cultural competence would improve the delivery of care to T2DM patients, while lack of consideration, or understanding, of a patients' culture was considered a hindrance in a New Zealand study [18]. Language, cultural, and religious competence add to positive interactions, realistic goal-setting, and tailored treatment plans [19][20][21]. The American Diabetes Association, the American Association of Diabetes Educators, and the Academy of Nutrition and Dietetics issued a joint statement in 2015 recommending treatment tailored to individuals and shared decision-making.…”
Section: Provider Knowledge and Expectationsmentioning
confidence: 99%